Viability PCR to detect the most-probable-number of viable probiotic bacteria in commercial preparations - Vasanthi, B; Nirmala, K; Tirumurugaan, K G; Rounak, Kumar; Alagumaruthanayagam, A; Dhinakar Raj, G; Raman, M (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The polymerase chain reaction (PCR) modification that enables molecular diagnosis and detection viable cells from diverse samples is based on the Viability PCR (V-PCR). In this study, we optimized V-PCR using a candidate L. plantarum probiotic strain and the technique performed efficiently in detecting live cells from an admixed suspension of live and dead cells. Application of the V-PCR on different probiotics strains (B. coagulans, L. plantarum and L. fermentum) also revealed a strong positive correlation in its performance across the strains tested even with an admixture of varied concentration of live and dead cells and different dilutions respectively (r=0.93 to 0.98). We obtained five and four commercial probiotics available for humans and animal use respectively from the market and tested for the recovery of total viable bacteria by agar pour plate method and also the count of viable bacteria by V-PCR. All commercial preparations when tested by the pour plate method recovered their listed viable counts except for the probiotic B and F, and C & G revealed lower counts (<1 to 2 log, and <3 to 4 log respectively) than the the manufacturer’s claims. A semi quantification approach using arbitrary density units with the universal 16S rRNA